2020
DOI: 10.7861/clinmed.2020-0012
|View full text |Cite
|
Sign up to set email alerts
|

Starvation ketoacidosis on the acute medical take

Abstract: Starvation ketoacidosis (SKA) represents one of three metabolic acidoses caused by the accumulation of ketone bodies within the bloodstream. While easily treated, it is a diagnosis that can be easily missed in patients with an unexplained metabolic acidosis. In this case report, we discuss two patients presenting with a starvation ketoacidosis and psychiatric illness. This link between SKA and psychiatric disease is especially pertinent as this is a cohort of patients who may not be able to give an accurate hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…However, such patients tend to have a low-to-normal blood glucose reading at presentation. 4 In our opinion, her weight loss and muscle wasting were more likely contributed by catabolic states observed in DKA.…”
Section: Differential Diagnosismentioning
confidence: 70%
“…However, such patients tend to have a low-to-normal blood glucose reading at presentation. 4 In our opinion, her weight loss and muscle wasting were more likely contributed by catabolic states observed in DKA.…”
Section: Differential Diagnosismentioning
confidence: 70%
“…Gall et al have reported two cases of SKA ( 9 ). The first patient was a 28 years old male patient with a known history of depression with a history of self-harm who presented to ED after being found in his room with a decreased level of consciousness.…”
Section: Discussionmentioning
confidence: 99%
“…She was treated first as DKA and received insulin with IV dextrose until the next day when she was diagnosed with SKA with suspicion of alcohol ketoacidosis (AKA). At that time, insulin was discontinued, and she was kept on IV dextrose with IV thiamine till improvement ( 9 ). Unlike our patient, these two patients had different causes of their HAGMA.…”
Section: Discussionmentioning
confidence: 99%
“…Ketones are often elevated in starvation as an alternate fuel source and can be sufficiently elevated to constitute a starvation ketoacidosis 58 . Alcoholism is a common comorbidity in cases of eating disorder–associated starvation, however, and alcoholic ketoacidosis may coexist with starvation ketoacidosis 58 . Because of low muscle mass, creatinine levels are often within normal or low ranges, despite a functionally low glomerular filtration rate, and must be kept in mind when considering renal impairment 8,59 …”
Section: Causes and Featuresmentioning
confidence: 99%
“…58 Alcoholism is a common comorbidity in cases of eating disorder-associated starvation, however, and alcoholic ketoacidosis may coexist with starvation ketoacidosis. 58 Because of low muscle mass, creatinine levels are often within normal or low ranges, despite a functionally low glomerular filtration rate, and must be kept in mind when considering renal impairment. 8,59 Testing for decreased serum prealbumin levels can be a useful indicator of starvation/undernourishment in the clinical and postmortem settings; however, serum albumin testing is unreliable and may actually be increased in dehydration.…”
Section: Ancillary Laboratory Investigationsmentioning
confidence: 99%